PERSPECTIVES OF INTRODUCTION THE STATE-PRIVATE PARTNERSHIP IN SPACE SPHERE OF UKRAINE - N.R. Malysheva; H.M. Hurova (Економіка та право)
The challenges facing public-private partnership in space activity domain of Ukraine are huge and multiply, so there imped it development. Public-private partnership expressed as primary guarantee of execution of the Concept of the National Scientific and Technical Space Program for 2018-2022 tasks, but there is no authority in National Space Agency of Ukraine, which could to ensure implementation of it mechanisms. Except this, according to Law of public-private partnership, only business enterprises with 100% of the authorized capital belonging to state could take part in public-private partnership. On the basis of tendency of privatization of such business enterprises, such legal provision is not enhancing public-private partnership in space activity of Ukraine. These and other problem issues push us to observe main directions to facilitate of analyzed legal relationships. Thus, it was studied charters of main Ukrainian space business enterprises, i. e. Khartron Public Company, Yuzhnoye Design Office etc., that have led to conclusions about expanding participation of such entities in publicprivate partnership. Initiation and active participation in public-private partnership of space enterprises with mixed (state and private) ownership are concerned as factor in ensuring of economic freedom in such sphere. Furthermore, it was critically researched procedures for the occurrence of public-private partnership and it was discovered their features in space activity. As a result, conclusion was made about key role of quality requirement to private candidates for entering into such kind of relationships in the absence of authorization requirement to space activity according to current legislation of Ukraine. Based on this, it was invited to upgrade legal regulation of authorization of space activity, assessment of impact on environment and space activity insurance.